La evasión tributaria originada en el uso de comprobantes de venta - Sánchez Fonseca, Javier Rodolfo (2017)
The present investigation had the purpose of analyzing the Ecuadorian billing regime and its incidence in tax evasion, within the study of the billing process is evidenced the improvements and technological advances that have had since the creation of SRI, as well as shortcomings that has the system and propose improvements, analyzed the control processes carried out by the SRI mainly in the misuse of sales vouchers that leads to the non-justification of expenses included in tax returns and therefore the damage that the taxpayer makes to the State . It also analyzed the laws that relate to the issue and its constant evolution since 2008 in which the tax system includes strong mechanisms to avoid tax evasion and fraud, such as the inclusion of banking and criminalize tax fraud a prisoner's trial and currently in the penal code, an analysis of the ghost companies project and the results obtained by the SRI are clearly present, clearly showing the variables of study of the investigation, their actual and practical application, and the incidence on tax collection, data obtained from the information available and requested from SRI and based on interviews with personnel of the Tax Audit and Tax Management departments that lead these processes in the IRS, which establishes a sector with greater risk of evasion by the misuse of the invoices and concluding that the taxpayer evades by unknown and to reduce their tax burden, since no one likes to pay taxes and also showed problems of smuggling that are related to the subject of study